PROSPEK PENGEMBANGAN EKONOMI SYARIAH DI MASYARAKAT BANJAR KALIMANTAN SELATAN - Ahmadi Hasan (AHKAM : Jurnal Ilmu Syariah, 2014)
Economic Development Prospects of Sharia in the Banjar Society in South Kalimantan. Currently Islamic economics, with a wide range of variants, is developing widely and dynamically. The development of Islamic finance has been extended to almost all parts of Indonesia, both in urban and rural areas. The Banjar tribe are a sub-ethnic group that inhabit the South Kalimantan area originating from the Malay coast. Islam is the foundation of culture and identity of the community of the Banjar. The presence of the Islamic economic concept in Banjar society is no longer unusual because Islamic values associated with it have become common place. The development of Islamic economics in Banjar society will continue to flourish if supported by government policy (top-down approach).DOI: 10.15408/ajis.v14i2.1281